THE ROLE OF THE WAQF PRACTICE IN FINANCING THE SOCIAL SECTOR - Bobur Valiyev; Firuz Abdullayev (Galaxy International Interdisciplinary Research Journal, 2022)
This article focuses on the development of the financial sector, the use of foundation practices in the harmonization of human and social development. The specifics of Islamic social finance are also analyzed. In addition, the requirements and benefits of waqf practice, the establishment of a waqf fund and their use in providing social assistance to the population are given.